Organizational Climate, Innovation Orientation, and Innovative Work Behavior: The Mediating Role of Psychological Safety and Intrinsic Motivation. (22nd March 2022) - Xu, Ziqing; Wang, Huilin; Suntrayuth, Sid
Abstract : Nowadays, many high-tech SMEs have gradually focused on innovation-orientation and have adopted various measures to create an organizational climate, stimulate knowledge workers' enthusiasm for innovation, and promote individual innovation behavior, but met with little success. Based on the stimulus organism response (SOR) model, the objective of this study is to explore the mediating factors that affect knowledge workers' innovative work behavior, and construct a three-level model of the external environment, psychological factors, and individual behavior. This study selected 575 valid samples from 24 high-tech SMEs in Zhongguancun, which is a technology hub in Haidian District, Beijing, China. Through the convenience sampling method, This study analyze the data and perform structural equation modeling (SEM) using AMOS 23.0. The external environment (i.e., organizational climate, innovation orientation) and psychological factors (i.e., intrinsic motivation, psychological safety) have a significant positive impact on innovative work behavior. Psychological factors have the most significant impact on innovative work behavior. Besides, psychological factors also mediate the relationship between the external environment and innovative work behavior. The findings indicated that high-tech SMEs need to formulate scientific innovation-orientation when implementing strategies, and continue to shape a harmonious and equal organizational climate. Furthermore, high-tech SMEs should encourage knowledge workers to speak the truth, express different voices, and stimulate work enthusiasm to improve psychological safety and intrinsic motivation, thereby enhancing knowledge workers' innovative work behavior.